2010
DOI: 10.1182/blood-2009-04-217224
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the p110β isoform of phosphoinositide 3-kinase in platelets reveals its central role in Akt activation and thrombus formation in vitro and in vivo

Abstract: During platelet activation, phosphoinositide 3-kinases (PI3Ks) produce lipid second messengers participating in the regulation of functional responses. Here, we generated a megakaryocyte-restricted p110␤ null mouse model and demonstrated a critical role of PI3K␤ in platelet activation via an immunoreceptor tyrosine-based activation motif, the glycoprotein VI-Fc receptor ␥-chain complex, and its contribution in response to Gprotein-coupled receptors. Interestingly, the production of phosphatidylinositol 3,4,5-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
121
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 21 publications
6
121
0
Order By: Relevance
“…The assumption that loss of PTEN in an incipient tumor acts to remove a "brake" from PI3K signaling raises the question of what signals provide the initial "foot on the accelerator." Because p110β is thought to be primarily required not for receptor tyrosine kinase (RTK) signaling but rather for G protein-coupled receptor (GPCR) or integrin signaling (22,(35)(36)(37), it is possible that the in vivo tumors studied here are responding to a local GPCR ligand, such as lysophosphatidic acid (LPA), arising either from the surrounding stroma or from an autocrine loop. However, we have no evidence for this in our system and, indeed, we found that LPA did not stimulate growth of the Pten-null OSE cells in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that loss of PTEN in an incipient tumor acts to remove a "brake" from PI3K signaling raises the question of what signals provide the initial "foot on the accelerator." Because p110β is thought to be primarily required not for receptor tyrosine kinase (RTK) signaling but rather for G protein-coupled receptor (GPCR) or integrin signaling (22,(35)(36)(37), it is possible that the in vivo tumors studied here are responding to a local GPCR ligand, such as lysophosphatidic acid (LPA), arising either from the surrounding stroma or from an autocrine loop. However, we have no evidence for this in our system and, indeed, we found that LPA did not stimulate growth of the Pten-null OSE cells in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of p110b, its negative effect lies at least in part in its role as a weak kinase competing with the more potent p110a isoform for binding sites on RTKs. Its positive function in certain tumors arising from PTEN loss may arise from a requirement for p110b in mediating signals downstream from particular activating inputs such as certain GPCRs or integrins (Hirsch et al 2000;Guillermet-Guibert et al 2008;Jia et al 2008;Ciraolo et al 2010;Martin et al 2010). Thus, it has been hypothesized that, in at least some PTEN loss-driven tumors, the signal activating PI3K comes from a GPCR.…”
Section: Discussionmentioning
confidence: 99%
“…One important intracellular pathway which regulates G i -dependent integrin αIIbβ3 activation is constituted by phosphoinositide 3-kinase (PI 3-K) [56, [67][68][69][70]. PI 3-K isoform p110β regulates integrin activation through a classical lipid kinase-dependent mechanism, involving the small GTPase Rap1 and/or the serine-threonine protein kinase B/Akt (PKB/Akt) [71][72][73][74][75][76], whereas p110γ appears to regulate integrin principally through a non-catalytic signalling mechanism [77,78]. Whether other PI3K class I isoforms such as the p110α or PI3K class II or III isoforms, which are highly expressed in blood platelets, play a role in integrin αIIbβ3 activation remains to be determined.…”
Section: Receptormentioning
confidence: 99%